1993
DOI: 10.1002/mrm.1910290602
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in the rat brain after acute and chronic ethanol intoxication: A 31P NMR spectroscopy study

Abstract: In this work, 31P phosphorus NMR (31P NMR) studies of the brain have been conducted in rats acutely and chronically intoxicated with ethanol. In both groups, changes in levels of high-energy phosphates were observed: increase of phosphocreatinine (PCr)/beta AaTP and PCr/inorganic phosphate (Pi) in acute and long-term ethanol exposure, and decrease of Pi/beta ATP after acute ethanol administration. These changes in high-energy phosphates, indicative of a reduction of adenosine triphosphate (ATP) and PCr consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
(5 reference statements)
4
17
1
Order By: Relevance
“…Reduced energy utilization has been documented in neuronal cell cultures in response to acute hypoxia [33] and in certain highly anoxia-tolerant species, such as turtles and fish [21]. Furthermore, it has been demonstrated that PCr concentration increases in the rat brain when cerebral energy consumption is suppressed by the ingestion of ethyl alcohol [14]. It is likely that chronic hypoxia in our model may have induced a similar effect on PCr.…”
Section: Discussionmentioning
confidence: 59%
“…Reduced energy utilization has been documented in neuronal cell cultures in response to acute hypoxia [33] and in certain highly anoxia-tolerant species, such as turtles and fish [21]. Furthermore, it has been demonstrated that PCr concentration increases in the rat brain when cerebral energy consumption is suppressed by the ingestion of ethyl alcohol [14]. It is likely that chronic hypoxia in our model may have induced a similar effect on PCr.…”
Section: Discussionmentioning
confidence: 59%
“…Preliminary results obtained for primary cultures of cortical neurons also showed no effects on the energetic status when these cells were subjected to 80 mM of ethanol up to 15 hr (data not shown). Denays et al (1993), however, reported a small transient increase in the PCr level in rat brain 60 -130 min after injection of a single dose of ethanol (equivalent to 21 mM of ethanol in the blood). This discrepancy may be merely due to the different experimental models used in the two studies.…”
Section: Discussionmentioning
confidence: 94%
“…22 Similar findings of tolerance to ethanol-induced changes in function after prolonged ethanol exposure have been reported after 3 or 8 weeks of daily ethanol intake in the diet. 47,50 Denays et al 82 assessed levels of high-energy phosphates, ATP, and phosphocreatinine among others, using 31 P phosphorus nuclear magnetic resonance ( 31 P-NMR) following 3 weeks of dietary ethanol. These investigators found indications of reduced high-energy phosphate consumption and by inference reduced cerebral metabolism after both acute and chronic exposure to ethanol.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Rodent studies of chronic alcohol exposure have either evaluated highdoses for short periods of time, usually on the order of days, 22,81 or low doses in the diet or drinking water for periods of a few weeks, 47,50,82 or a period of months to years. 83,84 Short-term experiments using the intra-arterial xenon method or the deoxyglucose method found that rats became tolerant after 3 to 4 days of nearly continuous intoxication to the effects of ethanol on CBF and cerebral metabolic rates for oxygen utilization, that is, fewer structures were affected by an acute dose of ethanol and to a lesser degree.…”
Section: Animal Studiesmentioning
confidence: 99%